Stuttering Disorder Therapy Using Aristotle’s Rhetoric Method In The King’s Speech Movie - Mas Alwis Imru'ul Qais As-syauqi; Slamet Setiawan (Department of English Language Education, UIN Sunan Ampel Surabaya, 2021)
Stuttering is a speech disorder that can be caused by many aspects such trauma, incident, and illness because there is no one born with this kind of speech disorder. The researcher in this study is focused on how Fluency Shaping Therapy and Stuttering Modification Therapy were used by Lionel, can reduce Bertie’s stuttering utterance. In addition, this study is using descriptive qualitative method to analyze and describe the data. Moreover, the data in this study is in the form of dialogues between Bertie and Lionel that were collected from The King’s Speech movie using analysis document. Then, the collected data is analyzed by data condensation, data analysis, and conclusion. The result shows that these two stuttering treatments (stuttering modification and fluency shaping which part of motor learning study) can be effective therapies because each of them has procedures that can support each other. In conclusion, stuttering is not an illness that human born along with but can be caused by many things and this speech disorder cannot be cured but can be reduced and modified using two methods, stuttering modification and fluency shaping therapy. Both of them can be combined together with Aristotle’s Rhetoric as a method to teach public speaking especially those who are having problems with stuttering.